The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1139/cjpp-2018-0111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA methyltransferase-1 instigates the expression of DNA methyltransferase-3a in angioplasty-induced restenosis

Abstract: Increased expression of DNA methyltransferase-1 (DNMT1) associates with the progression of many human diseases. Because DNMT1 induces cell proliferation, drugs that inhibit DNMT1 have been used to treat proliferative diseases. Because these drugs are nonspecific inhibitors of DNMT1, subsidiary events or the compensatory mechanisms that are activated in the absence of DNMT1 limit their therapeutic application. Here, we studied the molecular mechanisms that occur during angioplasty-induced restenosis and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…DNMT1 is an important enzyme implicated in DNA methylation, particularly in the promoter region of SOCS3. Moreover, CpG islands, one of which is located at kb 4.261-6.673 in the SOCS3 genomic locus, regulate DNMT1 function (27,28). miR-1264 downregulation facilitates persistent DNMT1 expression, thereby inducing SOCS3 promoter methylation and impacting its gene expression (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNMT1 is an important enzyme implicated in DNA methylation, particularly in the promoter region of SOCS3. Moreover, CpG islands, one of which is located at kb 4.261-6.673 in the SOCS3 genomic locus, regulate DNMT1 function (27,28). miR-1264 downregulation facilitates persistent DNMT1 expression, thereby inducing SOCS3 promoter methylation and impacting its gene expression (27).…”
Section: Discussionmentioning
confidence: 99%
“…The circRNA-0006896 network in UA exosomes increases the proliferation and migration of HUVECs. Previous studies have documented that DNMT1 is a critical regulator of JNK, STAT, and NF-κB signaling during the development of UA because an increase DNMT1 expression results in CpG island hypermethylation in the promoter region of SOCS3, which downregulates its expression (28). Low expression of SOCS3 promotes JNK/STAT signaling, thus increasing the proliferation and migration of HUVECs (29), which in turn leads to plaque destabilization and promotes AS development (23,30,31).…”
Section: Sa (N=22) Ua (N=20) Biological -----------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have identified two different molecular pathways of DNMT1 that work independently to repress the expression of a tumor suppressor protein, SOCS3, and promotes the development of neointimal hyperplasia [ 1 , 22 24 ]. Our continued research in this direction led us to explore interacting proteins and pathways which regulate DNMT1 activity during restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Our continued research in this direction led us to explore interacting proteins and pathways which regulate DNMT1 activity during restenosis. Further, we also reported that when DNMT1 expression was inhibited in VSMCs, its absence was supplemented by another isoform of DNMT, DNMT3a [ 24 ]. Since DNA methylation is a key mechanism by which gene expression is regulated in a controlled manner, the induction of subsidiary methylases, in absence of DNMT1, seems to be required for cell survival.…”
Section: Introductionmentioning
confidence: 99%